KONFLIK BATAS DESA ANTARA DESA PETANI DENGAN DESA SIMPANG PADANG KABUPATEN BENGKALIS - Rahmawati "; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In Indonesia, there are many problems with regional boundaries, problems up to village boundaries that overlap between one village and another. The problem of this research is the village boundary conflict between the Desa Petani and Desa Simpang Padang Kabupaten Bengkalis, which initially occurred because of the community's disobedience to village administration. This study aims to find out what are the factors that cause Village Boundary Conflicts between Desa Petani and Desa Simpang Padang and to find out how to resolve Village Boundary Conflicts between Desa Petani and Desa Simpang Padang.  The research approach used is a qualitative approach and the type of descriptive research. The location of this research was carried out in the Desa Petani and in the Desa Simpang Padang, and the data collection techniques were carried out by interviews and documentation. The results of this study are the factors causing the village boundary conflict between the Desa Petani and Desa Simpang Padang, namely the historical factor and the interest factor. To resolve the conflict, a form or effort is needed to resolve the village boundary conflict between the Desa Petani and Desa Simpang Padang. Efforts have been made to resolve the village boundary conflict between the Desa Petani and Desa Simpang Padang, namely by Negotiation and Mediation. However, the efforts made did not find a solution so that the conflict has not been resolved until now.  Keywords: Conflict, Village Boundaries